Uso de Levodopa para el tratamiento de la ambliopía: revisión de la literatura (2022)
Amblyopia is an alteration in the neurodevelopment of the visual system that is established during the first years of life. Its treatment begins with optical or surgical correction, as the case may be, and subsequently occlusion or penalization.